2005
DOI: 10.1021/ic0483996
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Computational Studies on [Ni(tmc)CH3]OTf:  Implications for Ni−Methyl Bonding in the A Cluster of Acetyl-CoA Synthase

Abstract: The five-coordinate high-spin (S = 1) Ni(2+) complex [Ni(tmc)CH(3)](+) (1) (tmc = 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane) serves as a model for a viable reaction intermediate of the A cluster of acetyl-CoA synthase (ACS) in which the distal nickel center is methylated. Spectroscopic and density functional theory (DFT) computational studies afford a quantitative bonding description for 1 that reveals a highly covalent Ni-CH(3) bond. From a normal coordinate analysis of resonance Raman data obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 53 publications
6
42
0
Order By: Relevance
“…The experimental Abs spectrum of 4 is dominated by a broad feature at 17,840 cm −1 that was initially assigned as a LMCT transition; this feature is well-reproduced in the TD-DFT calculated spectrum (note that the higher energy of the calculated band relative to its experimental counterpart reflects the tendency of TD-DFT to overestimate the energies of electronic transitions48,49). An analysis of the electron density difference map (EDDM) associated with this transition reveals that electron density is transferred primarily from the SR π(op) HOMO to the Ni 3d(x 2 −y 2 )-derived LUMO (Figure 7, panels b and c).…”
Section: Results and Analysismentioning
confidence: 65%
“…The experimental Abs spectrum of 4 is dominated by a broad feature at 17,840 cm −1 that was initially assigned as a LMCT transition; this feature is well-reproduced in the TD-DFT calculated spectrum (note that the higher energy of the calculated band relative to its experimental counterpart reflects the tendency of TD-DFT to overestimate the energies of electronic transitions48,49). An analysis of the electron density difference map (EDDM) associated with this transition reveals that electron density is transferred primarily from the SR π(op) HOMO to the Ni 3d(x 2 −y 2 )-derived LUMO (Figure 7, panels b and c).…”
Section: Results and Analysismentioning
confidence: 65%
“…Recent computational studies performed in our laboratory established that the proposed Ni-CH 3 and Co-CH 3 bonds are similarly strong (with M-CH 3 stretching force constants of 1.76 and 1.84 mdyn/Å, respectively), an intuitive requirement for the reversibility of the methylation. 84 This computational study also indicated that the conformational flexibility of the Ni site in ACS likely plays a significant role in promoting formation of the Ni-CH 3 bond. Thus, while the structural features of the A-cluster, which facilitate Ni-CH 3 bond formation, are becoming increasingly well understood, the mechanism by which CFeSP tunes the reactivity of its Me-Co 3+ corrinoid cofactor toward methyl-group transfer remained largely unknown.…”
Section: Methyl Group Transfer From Me-co 3+ Cfesp To the Acs A-clustermentioning
confidence: 63%
“…3 Recent advances in the area of Ni-O x complexes 4,5 have benefited from the accessibility of isolable Ni + precursors, sufficiently electron-rich to reduce dioxygen as demonstrated through spectroscopic studies of the resulting products. Specifically, efforts from these laboratories have led to the elucidation of Ni(η 2 -O 2 ), 6 Ni 2 (µ-1,2-O 2 ), 7,8 and Ni 2 (µ-O) 2 motifs. 9 The identity of the supporting ligand is critical both for the success in preparing the Ni + complexes and for directing the reactions toward variable product structures.…”
mentioning
confidence: 99%